La educación en la sociedad fenicia durante el i milenio a. C. - Martín Ruiz, Juan Antonio (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2025)
We aim to examine the available information on education in ancient Phoenicia and its colonies, which is not very abundant as literary and archaeological sources are relatively scarce but still allowing us to at least outline its main features. The system was based on an Eastern model, though infl uenced by the Greek educational sphere within the Hellenistic period, especially among the aristocratic status.